2021
DOI: 10.3390/nu13072251
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Tree Nuts and Peanuts with Adiposity Parameters: A Systematic Review and Network Meta-Analysis

Abstract: The network meta-analysis and systematic review conducted aim to comparatively assess the effects of tree nuts and peanuts on body weight (BW), body mass index (BMI), waist circumference (WC), and body fat percentage (BF%). A systematic search up to 31 December 2020 was performed. A random-effects network meta-analysis was conducted following the PRISMA-NMA statement. A total of 105 randomized controlled trials (RCTs) with measures of BW (n = 6768 participants), BMI (n = 2918), WC (n = 5045), and BF% (n = 1226… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 143 publications
2
20
0
Order By: Relevance
“…Although nuts are dense-energy foods, they are rich in micronutrients and bio-active compounds. Growing evidence suggests their role in protecting from obesity or helping in weight loss [52][53][54] due to several mechanisms including prolonged chewing, delayed gastric emptying because of fibers and unsaturated fats, increased satiety and booster actions on lipid oxidation and thermogenesis [55].…”
Section: Dietary Factors Associated With the Risk Of Obesitymentioning
confidence: 99%
“…Although nuts are dense-energy foods, they are rich in micronutrients and bio-active compounds. Growing evidence suggests their role in protecting from obesity or helping in weight loss [52][53][54] due to several mechanisms including prolonged chewing, delayed gastric emptying because of fibers and unsaturated fats, increased satiety and booster actions on lipid oxidation and thermogenesis [55].…”
Section: Dietary Factors Associated With the Risk Of Obesitymentioning
confidence: 99%
“…A 2014 review of epidemiological and RCT data concluded that evidence was lacking on the common assertion that regular consumption of nuts increased adiposity [ 10 ]. This was confirmed in a recent network meta-analysis of 105 RCTs comparing the effects of diets enriched in various tree nuts and peanuts vs. control diets on body weight, BMI, waist circumference (WC), and percent body fat [ 64 ]. No significant increase was observed in any adiposity measures with any of the nuts, except for hazelnut-rich diets, which raised WC.…”
Section: Nut Consumption and Health Outcomesmentioning
confidence: 77%
“…Due to the high energy density of nuts, increased body weight with long-term consumption has been an underlying concern. Yet, to the contrary, a growing body of epidemiological evidence suggests that daily nut consumption is a potentially effective strategy in the primary prevention of obesity [ 64 ].…”
Section: Nut Consumption and Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant literature searching was conducted following the Preferred Reporting Items for Systematic Reviews, and Meta Analyses (PRISMA) statement ( 25 , 26 ). The current study was registered on PROSPERO International Prospective Register of Systematic Reviews (CRD42021242213, April 11, 2021, https://www.crd.york.ac.uk/PROSPERO/ ).…”
Section: Methodsmentioning
confidence: 99%